2017
DOI: 10.1016/j.cognition.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

When attention wanders: Pupillometric signatures of fluctuations in external attention

Abstract: Attention is not always directed to events in the external environment. On occasion our thoughts wander to people and places distant from the here and now. Sometimes, this lack of external attention can compromise ongoing task performance. In the current study we set out to understand the extent to which states of internal and external attention can be determined using pupillometry as an index of ongoing cognition. In two experiments we found that periods of slow responding were associated with elevations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
123
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
3

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(136 citation statements)
references
References 67 publications
13
123
0
Order By: Relevance
“…Component Four places experiences with visual features ("images") in opposition to 514 experiences with verbal features ("monologue"), capturing dissociations between visual and 515 verbal thinking observed in our prior studies (Konishi et al, 2017;Medea et al, 2016;516 Smallwood et al, 2016). The accompanying neural pattern were associated with higher 517 connectivity between the visual network with other networks, in particular the limbic system.…”
mentioning
confidence: 99%
“…Component Four places experiences with visual features ("images") in opposition to 514 experiences with verbal features ("monologue"), capturing dissociations between visual and 515 verbal thinking observed in our prior studies (Konishi et al, 2017;Medea et al, 2016;516 Smallwood et al, 2016). The accompanying neural pattern were associated with higher 517 connectivity between the visual network with other networks, in particular the limbic system.…”
mentioning
confidence: 99%
“…In line with this idea, some studies found increased pupil baselines during mind-wandering (Franklin, Broadway, Mrazek, Smallwood, & Schooler, 2013), while others found lower baselines (e.g., Grandchamp, Braboszcz, & Delorme, 2014;Konishi, Brown, Battaglini, & Smallwood, 2017;Mittner et al, 2014;. Network reset theory, by contrast, predicts rapid adaptations around task switches.…”
Section: Pupil Changes Were Short-livedmentioning
confidence: 94%
“…(for examples see Konishi et al, 2017;Smallwood et al, 2016). This produced four components: (1) 'Detail', reflecting patterns of detailed visual task related experience, (2) 'Off-task thought', dissociating on task thought from episodic self-relevant thought, (3) 'Modality', distinguishing thoughts related to images or words and (4) 'Emotion' describing the affective tone of experiences.…”
Section: Categorising Experiencementioning
confidence: 99%